Board nationality diversity: its measurement, determinants, and impacts on firm value and accounting conservatism - Metwally, Tarek Mahmoud Mosaad (2021)
The composition of corporate boards has been under intense scrutiny by regulators since the collapse of Enron in 2002. An aspect of board composition is board diversity, which has gained the attention of regulators since 2003. Yet, empirical evidence on the outcomes of board diversity is inconclusive. One potential reason for the inconclusive results on board nationality diversity is that it has upside and downside aspects that should be accounted for simultaneously. In particular, I propose that any outcome of this diversity is the sum of the effects of two opposing forces: the level of diversity and the strength of cultural separation. Drawing on theories of resource dependence and groupthink, the level of dissimilarity in directors’ nationalities expands the pool of resources at the board’s disposal and mitigates the harmful behaviour of groupthink. However, nationality diversity among board members is accompanied by differences in their cultural backgrounds, which may serve as bases for cultural separation. This separation may cause poor communication, internal conflicts, and lack of trust between board members. The objective of this thesis is to provide a better understanding of how the above contrasting aspects of board nationality diversity may shape its outcomes. To this end, I distinguish between the upside and downside aspects of diversity in the first essay of this thesis. In this essay, I review the theoretical and empirical constructs of board diversity. I then introduce dissimilarity of director nationalities as a multi-categorical measure that accounts for the composition of foreign board members, to capture the level of board nationality diversity. The second essay investigates the determinants and the performance outcome of board nationality diversity, after accounting for its upside and downside aspects. Firm value is chosen to be the first outcome variable in this thesis as it is one of the most widely used proxies for board performance. In the third essay, accounting conservatism is chosen to be my second outcome variable. This is because diverse boards are found to adopt less risky financial policies. Therefore, I expect nationality-diverse boards and audit committees to demand greater accounting conservatism. The empirical tests in this thesis are based on large samples of UK firms over the period from 1999 to 2018. On the determinants of board nationality diversity, I find that the level of diversity is driven by the magnitude of foreign activities (measured by the proportion of foreign sales), rather than the number of geographical regions in which a firm operates. On the outcomes of board nationality diversity, I find that the level of diversity is associated with higher firm value. This association is not significantly mitigated by the strength of board cultural separation, but it is mitigated by the level of operational complexity. In addition, I find that levels of nationality diversity on the board and its audit committee positively impact accounting conservatism, whereas the strength of board cultural separation is not significantly related to accounting conservatism. This thesis makes five main contributions to the literature on board diversity, firm performance, and accounting conservatism. First, it proposes that the upside of diversity in multi-categorical attributes, such as nationality, is captured by the level of diversity. This level is maximized when each board member is unique in terms of the attribute under investigation. Second, it extends prior work on why foreign nationals exist on corporate boards by exploring why firms choose a given level of nationality diversity on their boards. Third, it accounts for both the positive and the negative aspects of board nationality diversity simultaneously, to identify its net impacts on firm value and accounting conservatism. Fourth, it provides robust evidence that board nationality diversity is positively associated with firm value and this association is moderated by levels of firm complexity. Fifth, it provides robust evidence that nationality diversity on the board and its audit committee positively impact accounting conservatism. The findings of this thesis have implications for board diversity in both research and practice. First, it suggests that both the positive and the negative aspects of board diversity should be accounted for simultaneously. Second, it reviews a set of theoretical and empirical constructs of diversity that could be applied to diversity within other workgroups (e.g., top management teams and audit teams). Third, it cautions against the use of empirical proxies that do not map onto the theoretical construct under investigation. Fourth, it directs companies’ attention to unique boards, in which, each board member is dissimilar to other board members in terms of a non-binary diversity attribute. This board structure maximizes (minimizes) the positive (negative) aspect of diversity in a non-binary attribute such as nationality. Fifth, it shows that board nationality diversity provides net benefits to shareholders only under certain circumstances (i.e., when firms are complex). Sixth, it identifies a new source of variation in accounting conservatism by providing robust evidence that nationality diversity on the board and its audit committee matter for conservatism in financial reporting. This study could therefore be of interest to academics, companies, investors, and regulators.